Urban agriculture and sanitation services in Accra, Ghana: the overlooked contribution - Lydecker, M.; Drechsel, Pay (Informa UK Limited, 2010)
While urban agriculture has long been valued for providing food security and nutrition within cities, it contributes to many other urban services that are seldom cited as rationales for protecting or even expanding urban food production. Articulating the actual and possible contributions of urban agriculture to municipal sanitation and health services is critical for sustaining these urban farms and their functions into the future. In the context of the low coverage and performance of wastewater treatment plants in Accra, Ghana, health risk reduction measures implemented on and off farm can substitute to a large extent for this absence of conventional wastewater treatment. We estimate that Accra generates approximately 80,000,000L of wastewater per day, of which urban vegetable farms alone use up to 11,250,000L. By mitigating the health risks for farmers and consumers associated with widespread wastewater irrigation, these urban farms have the potential to significantly contribute to the city's sanitation needs. This could allow partial outsourcing of public health services from treatment plants to the farm, where wastewater is considered an asset instead of a problem. Urban agriculture could also significantly support buffer zone management along streams and rivers, resulting in a reduction of solid waste dumping and environmental pollution, but most importantly an improvement in flood control and related public health challenges. While urban agriculture is not the panacea for addressing these urban challenges, it can significantly contribute to their solution.